Comments on the paper “Efficacies of globus pallidus stimulation and subthalamic nucleus stimulation for advanced Parkinson’s disease: a meta-analysis of randomized controlled trials” - Negida A (Dove Medical Press, 2016)
Ahmed Negida,1 Doaa Attia2 1Faculty of Medicine, Zagazig University, Zagazig, Egypt; 2Faculty of Medicine, Alexandria University, Alexandria, EgyptWe read with interest the article by Tan et al,1 in which they meta-analyzed data of randomized controlled trials to compare subthalamic and pallidal deep brain stimulation for Parkinson’s disease (PD). Although the topic is interesting and important, we found three serious statistical errors in the article.View original paper by Tan and colleagues.